A Newly Discovered Humic-Reducing Bacterium, Pseudomonas geniculata PQ01, Isolated From Paddy Soil Promotes Paraquat Anaerobic Transformation - Wu, Chunyuan; Wu, Xiaoyan; Chen, Shanshan; Wu, Dongming (Frontiers in Microbiology, 2020)
Due to toxicity and persistence of paraquat (a widely used herbicide), eco-friendly remediation approaches to its contamination and effective antidotes to its poisoning have been highly desired and raised increasing concerns. Paraquat degradation was lesser in aerobic soil in comparison to anaerobic soil, humic-reducing microorganism play a key role in paraquat anaerobic transformation process. However, the degradation pathways and related mechanisms remain poorly understood. In this study, we investigated the specific interaction mechanisms of the paraquat transformation processes mediated by a humic-reducing strain under anaerobic conditions. A strain of pure culture, designated as PQ01, was successfully isolated from paddy soil using anaerobic enrichment procedure, and identified as Pseudomonas geniculata using phenotypic and phylogenetic analysis. Sucrose, glucose, pyruvate, formic acid and acetic acid were the favorable electron donors for anthrahydroquinone-2,6-disulfonate (AQDS) reduction by the strain PQ01; the strain had the ability of reducing Fe(III) (hydr)oxides in the presence of sucrose and its Fe(III) reducing capacity ranked as ferrihydrite > α-FeOOH/γ-FeOOH > γ-Fe2O3 > α-Fe2O3. In the system of “PQ01 + paraquat + AQDS + sucrose”, AQDS reduction and paraquat biotransformation by strain PQ01 occurred simultaneously, and the presence of sucrose would significantly enhance the biotransformation. Specific mechanisms of the electron transfer processes promoted by both PQ01 and AQDS, and proceed in two aspects: (1) paraquat served as electron donor in the anaerobic reduction of AQDS by strain PQ01; (2) AQDS was reduced by PQ01 anaerobic metabolism to produce AH2QDS, which can directly react with paraquat under anaerobic conditions to generate a single crystal compound (molecular formula of unit structure is C26H20N2O8S2), leading to paraquat declined dramatically. In conclusion, this main mechanism included the microbial reduction of AQDS to AH2QDS, followed by the abiotic reaction between AH2QDS and paraquat. This study reported the new characteristics of Pseudomonas geniculata capable of reducing humics analogues, Fe(III) (hydr) oxides and paraquat, and proposed a novel electron transformation mechanism of organic contaminant degrading mediated by humic-reducing microorganisms.